Dynamic Changes in Microbial Communities and Physicochemical Characteristics During Fermentation of Non-post Fermented Shuidouchi - Chen, Yuyong; Qin, Feng; Dong, Mingsheng (Frontiers in Nutrition, 2022)
Non-post fermented Shuidouchi is a Chinese spontaneously fermented soybean food with multifunctionality in human health. The functionality and safety of this plant-based food will be affected by the microorganisms during fermentation. In this study, microbial diversity was investigated using culture-dependent and culture-independent methods. The functional metabolites such as polyamines and alkylpyrazines were also determined at different time points during fermentation. We found that Bacillus was the most dominant microbe throughout the fermentation process, while the temperature was the most important influencing factor. During fermentation, the microbial diversity increased at a moderate temperature and decreased at a high temperature (52°C). High temperature caused the prosperity of the spore-producing bacteria such as Bacillus (more than 90% relative abundance in bacteria) and Aneurinibacillus (2% or so relative abundance in bacteria), and the inhibition of fungi. Furthermore, it was found by correlation analysis that the relative abundances of Bacillus and Aneurinibacillus were positively correlated with the relative content of amino acid metabolism pathway and the content of most alkylpyrazines and biogenic amines. Meanwhile, the relative abundances of many non-dominant bacteria were negatively correlated with the content of biogenic amines and positively correlated with the relative content of carbohydrate metabolism pathway. These effects were helpful to control the biogenic amine contents under the safety limits, increasing the alkylpyrazine type and product functionality. A two-stage temperature control strategy—a moderate temperature (35°C to 42°C) first, then a high temperature (52°C)—was concluded from the spontaneous fermentation of non-post fermented Shuidouchi. This strategy could improve the safety of product by inhibiting or sterilizing the thermolabile microbes. The non-post fermented Shuidouchi product is rich in functional compounds such as polyamines and alkylpyrazines.